8. Kajian Budidaya Ikan Rainbouw (Melanotaenia parva) di Balai Penelitian dan Pengembangan Budidaya Ikan Hias Depok, Jawa Barat - Herman Yulianto; Fadli Dzil Ikrom (Fakultas Perikanan Universitas Pekalongan, 2016)
Rainbow fish (Melanotaenia parva) is original endemic fish originated from Papua. This fish is fancied due to its beauty and uniqueness. The purposes of this general practice of rainbow fish (Melanotaenia parva) seeding were the following: (1) to learn the qualified and interesting method of raising of parents, larva, and seedlings of rainbow fish (Melanotaenia parva) originated from Kurumoi Lake; (2) to identify and solve any problems occurring during the activities of general practice of rainbow fish (Melanotaenia parva) such as diseases, pests, and mortality. The method of activities by collecting primary and secondary data using literature approach, observation, interview, and direct practice. The activities were conducted on 1 July until 1 August 2013 in Ornamental Fish Development and Research of Depok, West Java. The process of rainbow fish seeding included the process of parent raising, parent selection, spawning, egg raising, and larva and fry raising. Some matters determining the seeding were contained preparation, water quality handling, feed management, and pest and disease control. Keyword : Rainbow, Ornamental fish